Results 1 to 3 of 3

Math Help - F(a-b)=f(a)-f(b)

  1. #1
    Super Member
    Joined
    Sep 2013
    From
    Portland
    Posts
    539
    Thanks
    73

    F(a-b)=f(a)-f(b)

    Let X and Y be sets, and let A and B be any subsets of X.Determine if for all functions from X to Y, F(A-B) = F(A) - F(B) Justify your answer

    intuition tells me no because the F(A-B) will have a different x values going to a different y values in Y than F(A) - F(B)

    also,

    the left side will have x values from X such that they are in A \cap B^c

    whereas the right side would have x values from X such that they are in A \cup B

    and clearly A \cap B^c \neq A \cup B
    Follow Math Help Forum on Facebook and Google+

  2. #2
    Super Member
    Joined
    Sep 2013
    From
    Portland
    Posts
    539
    Thanks
    73

    Re: F(a-b)=f(a)-f(b)

    maybe I should do a counterexample along with it

    let A = {1,2,3,4,5} and B = {1,3,5,6,7}

    and have the function y = x^2

    then
    F(A-B) = {4,16}

    F(A) - F(B) = {0,-8,-24,-35,-48......}
    Follow Math Help Forum on Facebook and Google+

  3. #3
    MHF Contributor

    Joined
    Apr 2005
    Posts
    16,449
    Thanks
    1864

    Re: F(a-b)=f(a)-f(b)

    Quote Originally Posted by Jonroberts74 View Post
    maybe I should do a counterexample along with it

    let A = {1,2,3,4,5} and B = {1,3,5,6,7}

    and have the function y = x^2

    then
    F(A-B) = {4,16}
    To get "{" and "}" in latex, you need to use "\{" and "\}"
    F(A- B)= F(\{2, 4\})= \{4, 16\}
    Yes, that is correct.

    F(A) - F(B) = {0,-8,-24,-35,-48......}
    But now you have suddenly changed your definition of "-". For sets "X- Y" is defined as "all those members of X that are not in Y". It does NOT mean "subtract members of Y from members of X"!
    F(A)= \{1, 4, 9, 16, 25\}. F(B)= \{1, 9, 25, 36, 49\}

    So F(A)- F(B)= \{4, 16\} again. This is not a "counter-example".
    Follow Math Help Forum on Facebook and Google+

Search Tags


/mathhelpforum @mathhelpforum